Local Management of Anogenital Warts in Non-immunocompromised Adults: A Systematic Review and Meta-analyses of Randomized Controlled Trials - Antoine Bertolotti; Brigitte Milpied; Sébastien Fouéré; Nicolas Dupin; André Cabié; Christian Derancourt (Adis, Springer Healthcare, 2019)
Abstract Introduction Several therapeutic options are available to manage anogenital warts (AGWs). However, no hierarchy of treatments is provided in the latest European and American recommendations. This study aimed to determine the efficacy and safety of local treatments for the management of AGWs. Methods A search was conducted through 12 databases from inception to August 2018. All randomized controlled trials (RCTs) in which at least one parallel treatment group composed of immunocompetent adults with AGWs received at least one provider-administered or patient-administered treatment were included. Risk of bias assessment and meta-analyses of aggregated study data were performed on the basis of the Cochrane Handbook, and quality of evidence evaluation followed the Grading of Recommendation Assessment, Development and Evaluation (GRADE) approach. Primary endpoints were complete clearance and recurrence at 3 months. Results Seventy RCTs (9931 patients) were included. All but four RCTs had a high risk of bias. CO2 laser was slightly more efficacious than cryotherapy [risk ratio (RR) 2.05; 95% confidence interval (CI) 1.61-2.62], with fewer recurrences at 3 months (RR 0.28; 95% CI 0.09-0.89). Electrosurgery was slightly more efficacious than cryotherapy. No differences in efficacy or side effects were found between cryotherapy and imiquimod or trichloroacetic acid. Podophyllotoxin gel was slightly more efficacious than podophyllotoxin cream. 5-Fluorouracil (5-FU) was slightly more efficacious and caused less erosion than CO2 laser (RR 1.37; 95% CI 1.11-1.70). Conclusion The vast majority of included RCTs had a low level of evidence, thereby preventing the establishment of a hierarchy of treatments. Nevertheless, our results provide an overview of the main AGW treatments available for general practitioners and specialists. While provider-administered treatments are superior, patient-administered treatments (e.g., imiquimod, podophyllotoxin) are useful solutions for compliant patients. Protocol registration PROSPERO-CRD42015025827.